ALLOMETRIC SCALING OF VO2max: A SYSTEMATIC REVIEW AND META-ANALYSIS. Issue 22 (1st November 2016) - Lolli, L; Batterham, AM; Weston, KL; Atkinson, G
Abstract : We aimed to provide the first quantitative synthesis of derived static allometric coefficients ( b ) used for scaling maximal oxygen uptake (VO2max ) to whole-body mass and fat-free mass in human samples. Eight electronic databases were searched for relevant peer-reviewed articles. Inclusion criteria comprised human cardiorespiratory fitness data; cross-sectional study designs; an empirical derivation of the exponent; reported precision statistics; and reported information regarding participant sex, age and sports background, VO2max protocol, body composition protocol and line-fitting methods. Thirty-seven studies, involving 7, 851 participants, met the eligibility criteria and were dichotomized into two main domains relevant to whole-body mass (n=28) and fat-free mass (n=16), respectively. The pooled allometric exponent (95% CL) was found to be 0.71 (0.65 to 0.77) for body mass and 0.91 (0.83 to 0.98) for fat-free mass. The among-studies heterogeneity was substantial for both whole-body mass and fat-free mass (τ =±0.15). Participant sex explained 33% of the between-study variability in the whole body mass exponent, but only 5% of the variability in the fat-free mass exponent. While the body mass exponent was substantially lower in women ( b =0.52; 95% CL: 0.41 to 0.64) than for men ( b =0.77; 95% CL: 0.71 to 0.83), the fat-free mass exponent was similar for both sexes. None of the identified moderator variables was statistically significant. The body mass exponent estimate encompassed both ⅔- and ¾-power laws. Conversely, the fat-free mass exponent was substantially larger and more generalisable due to the heterogeneity of body composition in human samples. We conclude that the scaling of VO2max in humans is consistent with the allometric cascade model, with an estimated pooled exponent that precludes ⅔- and ¾-power scaling.